A porous spheroidal biphasic ceramic material and a method for its production

CN122916645APending Publication Date: 2026-10-16XIAN THERMAL POWER RES INST CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611214326.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]现有热化学制燃料材料多以粉末或不规则颗粒形式存在,在固定床、移动床或流化床反应器中容易出现床层压降较大、气固接触不均匀、颗粒团聚和传质阻力较大的问题

Benefits of technology

本发明通过La0.9Ca0.1FeO3钙钛矿相作为主要氧化还原活性相,Gd0.2Ce0.8O2萤石相作为氧迁移促进相和结构稳定相,二者复合形成双相陶瓷结构,使得材料兼具钙钛矿氧化还原活性和Ce基氧化物氧迁移能力,提高了热化学制燃料过程中的氧交换性能和高温结构稳定性;通过所述多孔球状双相陶瓷材料具有球状或近球状形貌,相比粉末材料更适合固定床、移动床或流化床反应器应用,能够降低床层压降并改善气固接触均匀性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916645A_ABST
    Figure CN122916645A_ABST
Patent Text Reader

Abstract

The application discloses a kind of porous spherical two-phase ceramic materials and preparation method thereof, belong to solar thermal chemical fuel material technical field.The porous spherical two-phase ceramic material includes La0.9Ca0.1FeO3 perovskite phase and Gd0.2Ce0.8O2 fluorite phase, two composite form two-phase ceramic structure;The porous spherical two-phase ceramic material has spherical or near spherical morphology, and internal with porous structure.Its preparation method includes: respectively preparing La0.9Ca0.1FeO3 perovskite powder and Gd0.2Ce0.8O2 fluorite phase powder;Two composite ball milling to obtain two-phase powder;Polyvinyl butyral ethanol solution is prepared;Two-phase powder, polyvinyl butyral ethanol solution and polyethylene glycol are mixed and grinded to obtain plastic mud material;Strand is twisted and placed in ball former and is formed into mud spherical particle;Drying and calcining, it is obtained.The application material has redox activity and oxygen migration ability, spherical shape and porous structure improve gas-solid contact and gas diffusion, preparation method equipment is simple, cost is low, and ball diameter and porosity can be adjusted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solar thermochemical fuel production technology, and relates to a porous spherical dual-phase ceramic material and its preparation method. Background Technology

[0002] Solar thermochemical fuel production technology utilizes high-temperature thermal energy to drive reversible redox reactions in metal oxides, converting water vapor or carbon dioxide into hydrogen, carbon monoxide, or syngas. This is a crucial technological route for achieving high-grade solar energy conversion and chemical storage. In this process, the oxide material releases lattice oxygen and forms oxygen vacancies during the high-temperature reduction stage, which then reacts with H2O, CO2, or a H2O / CO2 mixture during the oxidation stage to generate H2, CO, or syngas.

[0003] Perovskite oxides possess the advantages of tunable composition, controllable oxygen vacancy concentration, and good thermal stability, making them promising candidates for thermochemical fuel production. Among them, LaFeO3-based perovskite materials, after Ca doping, exhibit adjustable defect structures and redox properties. Gd-doped CeO2 materials demonstrate good oxygen ion conductivity and can serve as oxygen exchange and structural stabilizing components. Therefore, combining La0.9Ca0.1FeO3 with Gd0.2Ce0.8O2 is expected to improve the oxygen migration capacity, reactivity, and structural stability of the material during thermochemical cycling.

[0004] Existing thermochemical fuel materials are mostly in powder or irregular particle form, which easily leads to problems such as large bed pressure drop, uneven gas-solid contact, particle agglomeration, and high mass transfer resistance in fixed-bed, moving-bed, or fluidized-bed reactors. Furthermore, powder materials are prone to sintering and pore structure collapse during high-temperature cycling, resulting in decreased reactivity and cycling stability. In addition, existing methods for preparing spherical ceramic particles typically require spray granulators, extrusion spheronizers, or dedicated granulation equipment, which are costly and involve complex processes, hindering the rapid laboratory preparation of spherical ceramic particles of different diameters. Summary of the Invention

[0005] The purpose of this invention is to provide a porous spherical dual-phase ceramic material and its preparation method to solve the above-mentioned problems.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a porous spherical dual-phase ceramic material, comprising: La 0.9 Ca 0.1 FeO3 perovskite phase and Gd 0.2 Ce 0.8O2 fluorite phase, the two are combined to form a two-phase ceramic structure; the porous spherical two-phase ceramic material has a spherical or near-spherical morphology and a porous structure inside.

[0007] Furthermore, the diameter of the porous spherical dual-phase ceramic material is 1-5 mm.

[0008] Furthermore, the porous structure is formed by the thermal decomposition of polyvinyl butyral and polyethylene glycol during calcination.

[0009] Furthermore, the porous spherical dual-phase ceramic material is used in thermochemical fuel production reactions, including steam cracking to produce hydrogen, carbon dioxide cracking to produce carbon monoxide, or co-cracking of steam and carbon dioxide to produce syngas.

[0010] Secondly, the present invention provides a method for preparing the aforementioned porous spherical dual-phase ceramic material, comprising the following steps: S1, Preparation of La 0.9 Ca 0.1 FeO3 perovskite powder; S2, Preparation of Gd 0.2 Ce 0.8 O2 fluorite phase powder; S3, the La 0.9 Ca 0.1 FeO3 perovskite powder and the Gd 0.2 Ce 0.8 O2 fluorite phase powder was subjected to composite ball milling to obtain La 0.9 Ca 0.1 FeO3- Gd 0.2 Ce 0.8 O2 biphase powder; S4. Prepare a polyvinyl butyral ethanol solution; S5. Mix and grind the biphase powder, polyvinyl butyral ethanol solution and polyethylene glycol to obtain a plastic mud-like material; S6. Roll the mud-like material into strips and place them in a ball-forming machine to form mud-like spherical particles; S7. Dry the mud-like spherical particles to obtain dried spherical particles; S8. The dried spherical particles are calcined to obtain the porous spherical dual-phase ceramic material.

[0011] Furthermore, in step S1, The La 0.9 Ca 0.1FeO3 perovskite powder is prepared by the following steps: La₂O₃, CaCO₃, and Fe₂O₃ powders are weighed according to a molar ratio of La:Ca:Fe of 9:1:10. Anhydrous ethanol and grinding balls are added, and the mixture is ball-milled. The ball-milled slurry is dried, calcined, and ground to obtain La₂O₃ powder. 0.9 Ca 0.1 FeO3 perovskite powder.

[0012] Furthermore, in step S2, The Gd 0.2 Ce 0.8 O2 fluorite phase powder was prepared by the following steps: Gd2O3 and CeO2 powders were weighed according to a molar ratio of Gd to Ce of 2:8, anhydrous ethanol and grinding balls were added, and the mixture was ball-milled. The ball-milled slurry was dried, calcined, and ground to obtain Gd2O3 powder. 0.2 Ce 0.8 O2 fluorite phase powder.

[0013] Furthermore, in step S3, the La 0.9 Ca 0.1 FeO3 perovskite powder and Gd 0.2 Ce 0.8 The mass ratio of O2 fluorite phase powder is 1:1.

[0014] Furthermore, in step S5, the La 0.9 Ca 0.1 FeO3- Gd 0.2 Ce 0.8 The mass ratio of O2 duplex powder, polyvinyl butyral ethanol solution, and polyethylene glycol is 6:3:1, and the mass fraction of the polyvinyl butyral ethanol solution is 5%. The porosity of the final porous spherical duplex ceramic material can be controlled by adjusting the proportion of polyvinyl butyral ethanol solution added.

[0015] Furthermore, the forming diameter of the ball-making device is 1-5 mm, and porous spherical dual-phase ceramic materials with different ball diameters can be prepared by replacing the ball-making device with a different diameter; the ball-making device is prepared by 3D printing.

[0016] Compared with the prior art, the present invention has the following technical effects: This invention utilizes a La0.9Ca0.1FeO3 perovskite phase as the main redox active phase and a Gd0.2Ce0.8O2 fluorite phase as the oxygen migration promoting and structural stabilizing phase. The two phases are combined to form a dual-phase ceramic structure, giving the material both perovskite redox activity and Ce-based oxide oxygen migration capability, thus improving oxygen exchange performance and high-temperature structural stability in thermochemical fuel production processes. Furthermore, the porous spherical dual-phase ceramic material has a spherical or near-spherical morphology, making it more suitable for fixed-bed, moving-bed, or fluidized-bed reactor applications compared to powder materials, thereby reducing bed pressure drop and improving gas-solid contact uniformity. The porous structure, formed by the thermal decomposition of polyvinyl butyral and polyethylene glycol during calcination, facilitates the diffusion of reactant gases within the particles, thereby increasing the thermochemical reaction rate. This preparation method, for the first time, employs a step of shaping the pellets into balls using a pelletizing machine, avoiding the need for spray granulators, extrusion spheroidizers, or other specialized granulation equipment. This achieves simple, convenient, and low-cost preparation of spherical particles. By changing the pelletizing machine to different diameters, porous ceramic microspheres of varying diameters can be easily prepared, allowing for particle size adjustment based on different reactor configurations and bed requirements, resulting in high process flexibility. By adjusting the proportion of polyvinyl butyral ethanol solution added, the porosity of the final porous spherical ceramic material can be controlled, and the pore structure can be adjusted, which is beneficial to optimize gas diffusion and reaction activity according to the requirements of thermochemical fuel production reaction. The combined effect of the above materials and methods makes the present invention have significant application advantages in fixed bed, moving bed or fluidized bed thermochemical fuel production reactors. Attached Figure Description

[0017] Figure 1 This is a flowchart of the preparation process. Detailed Implementation

[0018] The present invention will now be described in further detail with reference to the accompanying drawings: Example 1, see Figure 1 In one embodiment of the present invention, a method for preparing porous spherical dual-phase ceramic materials is provided to solve the problems of large bed pressure drop, high mass transfer resistance, insufficient gas-solid contact, easy particle agglomeration, and insufficient high-temperature cycling stability of existing powdered thermochemical fuel materials. At the same time, it solves the problems of high equipment cost, complex process, and difficulty in flexibly controlling spherical diameter and porosity in existing spherical ceramic particle preparation methods.

[0019] Specifically, the preparation method of the porous spherical dual-phase ceramic material of the present invention includes the following steps: S1: Preparation of La0.9Ca0.1FeO3 perovskite powder; S2: Preparation of Gd0.2Ce0.8O2 fluorite phase powder; S3: The La0.9Ca0.1FeO3 perovskite powder and the Gd0.2Ce0.8O2 fluorite phase powder are ball-milled to obtain La0.9Ca0.1FeO3-Gd0.2Ce0.8O2 biphase powder; S4: Prepare a polyvinyl butyral ethanol solution; S5: Mix and grind the biphase powder, polyvinyl butyral ethanol solution and polyethylene glycol to obtain a plastic mud-like material; S6: Roll the mud-like material into strips and place them in a ball-forming machine to obtain mud-like spherical particles; S7: Dry the mud-like spherical particles to obtain dried spherical particles; S8: The dried spherical particles are calcined to obtain the porous spherical dual-phase ceramic material.

[0020] Step S1 involves preparing La0.9Ca0.1FeO3 powder with a perovskite crystal structure, which will serve as the main redox active phase in the final composite material. Perovskite oxides are a class of composite metal oxides with the general ABO3 formula, where the A-site is typically occupied by rare earth or alkaline earth metal ions, and the B-site by transition metal ions. LaFeO3-based perovskite materials have potential applications in thermochemical fuel production due to their tunable composition, controllable oxygen vacancy concentration, and good thermal stability. This is achieved by doping LaFeO3 with Ca at the A-site, i.e., using Ca²⁺... + Partially replaces La³ + Doping can effectively regulate the defect chemical properties and redox performance of materials. To maintain electroneutrality, oxygen vacancies or valence state changes occur in the material after doping, thus affecting its ability to release and replenish lattice oxygen. This doping strategy is one of the key means to improve the reactivity and cycle stability of materials in solar thermochemical cycles. For example, in a specific implementation of this invention, the subscripts 0.9 and 0.1 in La0.9Ca0.1FeO3 represent the atomic molar ratio of La and Ca.

[0021] In step S2, this step is used to prepare Gd0.2Ce0.8O2 powder with a fluorite-type crystal structure. This powder will serve as the oxygen migration-promoting phase and structurally stabilizing phase in the final composite material. Fluorite-type oxides, such as CeO2, possess unique oxygen ion conductivity, with rapid oxygen ion diffusion channels existing within their crystal lattice. By doping CeO2 with Gd, the oxygen vacancy concentration can be further increased, significantly enhancing its ionic conductivity. In this invention, the main role of the Gd0.2Ce0.8O2 fluorite phase is to act as a rapid oxygen transport channel during thermochemical cycling, promoting the migration of bulk oxygen to the reaction interface, thereby improving the oxygen storage and release capacity of the entire composite material. Simultaneously, the fluorite phase exhibits excellent high-temperature stability and can serve as a structural framework, inhibiting the sintering and agglomeration of perovskite particles (the active phase) during repeated high-temperature redox cycles, thus playing a role in structural stability. For example, the atomic molar ratio of Gd to Ce in Gd0.2Ce0.8O2 is 2:8.

[0022] For step S3, the La0.9Ca0.1FeO3 perovskite powder and Gd0.2Ce0.8O2 fluorite phase powder prepared separately are uniformly mixed and mechanically activated by a composite ball milling process.

[0023] Ball milling is not merely a simple physical mixing process. During high-energy ball milling, the repeated impact, shearing, and friction of the grinding balls on the powder particles lead to particle refinement, the creation of lattice defects and fresh surfaces, achieving mechanical alloying of the two powders. This thorough mixing at the microscale is fundamental for the high-quality composite formation of the two powders into a dual-phase ceramic structure during the subsequent calcination stage. If the two powders are not mixed uniformly, local enrichment of the perovskite and fluorite phases will occur in the final material, failing to fully utilize the oxygen migration-promoting and structural stabilizing effects of the fluorite phase on the perovskite phase. Therefore, the composite ball milling process in this step is a crucial step determining the consistency and reliability of the final material's properties. Through this step, a La0.9Ca0.1FeO3-Gd0.2Ce0.8O2 dual-phase powder precursor is obtained, characterized by a tight microscale mixture and composite of the two original powders.

[0024] In step S4, this step is used to prepare an ethanol solution of polyvinyl butyral as a binder, molding aid, and pore-forming component in subsequent steps. Polyvinyl butyral is a commonly used polymer with good adhesion, film-forming properties, and flexibility. Dissolving it in anhydrous ethanol forms a homogeneous solution with a certain viscosity. Anhydrous ethanol is chosen as the solvent because it has good solubility for polyvinyl butyral and its surface tension is moderate, making it easy to wet the surface of ceramic powder particles. More importantly, ethanol is easily volatilized and removed in the subsequent drying step, leaving no harmful residues. Polyvinyl butyral plays a dual role here: in the molding stage, it acts as a binder, imparting plasticity to the mud-like material, allowing it to be rolled and shaped, and providing sufficient green strength to the spherical particles after drying; in the calcination stage, polyvinyl butyral undergoes thermal decomposition at high temperatures, producing gaseous products such as carbon dioxide and water through oxidation reactions, which escape and leave pores, thus acting as a pore-forming agent. This multi-purpose design simplifies the process and material system.

[0025] In step S5, the biphasic powder, polyvinyl butyral ethanol solution, and polyethylene glycol are mixed and thoroughly ground to prepare a slurry material with good plasticity. Polyethylene glycol is used as a binder in this invention to further improve the plasticity of the slurry material, making it less prone to cracking, breaking, or crumbling during subsequent rolling and kneading molding. Polyethylene glycol itself is also a high-molecular-weight organic compound with lubricating and binding properties. Like polyvinyl butyral, it undergoes complete thermal decomposition during high-temperature calcination, collectively forming and regulating the porous structure within the material. The state of the plastic slurry material is crucial: if the slurry is too thin, it cannot be rolled into strips or maintain a spherical shape in a baller; if the slurry is too dry, it loses its adhesiveness and crumbles into powder during rolling and kneading, making it unsuitable for molding. Therefore, by precisely controlling the proportions of each component, especially the amount of polyvinyl butyral ethanol solution added, the plasticity of the slurry material can be effectively adjusted to precisely meet molding requirements.

[0026] For step S6, a two-step physical method of "strip rolling-ball forming" is used to prepare spherical particles. First, the plastic mud-like material obtained in step S5 is rolled into thin strips with a diameter of 1-5 mm, and then placed into a ball forming tool. The ball forming tool is a forming tool with a hemispherical or similar shaped groove of a specific diameter. By kneading or rolling the two opposing parts, the strip-shaped material is gathered and corrected into spherical or near-spherical particles. This forming method completely imitates the operation principle of making spherical pills by hand, but it is standardized and tool-based. Its biggest technical advantage is that the whole process does not require any high-cost special granulation equipment, such as spray granulators or extrusion rounding machines. Spray granulators are large, energy-intensive, and have complex process parameters; extrusion rounding machines integrate two functional modules, extrusion and rounding, and have a complex structure and are expensive. The ball forming tool used in this invention is extremely simple to manufacture and can even be obtained at low cost and quickly through 3D printing technology. This greatly reduces the technical and economic threshold for the preparation of spherical ceramic particles, and is especially suitable for laboratory research and rapid preparation of small batches and multiple varieties.

[0027] In step S7, the mud-like spherical particles obtained in step S6 are dried to remove most of the solvent (anhydrous ethanol) and excess water from the particles, thus giving them initial mechanical strength. This step is typically performed in a drying oven at a suitable temperature to allow the solvent to evaporate uniformly at a controlled rate. If the drying speed is too fast, the particle surface will rapidly shrink and form a crust due to the rapid evaporation of the solvent, while the internal solvent has not yet been expelled, which can easily lead to cracking or deformation of the particles. Therefore, controlling the drying temperature and the heating program is crucial. After drying, the mud-like spherical particles will be transformed into dry spherical particles. At this point, polyvinyl butyral and polyethylene glycol, acting as binders, have solidified, forming a polymer network of bonding bridges between the powder particles. This gives the dry spherical particles sufficient green strength to withstand the mechanical impacts of subsequent operations such as transfer and stacking without breaking.

[0028] Step S8 is the final high-temperature heat treatment process, during which a series of complex physicochemical changes occur, ultimately forming the target product. The dried spherical particles are placed in a muffle furnace or tube furnace and calcined at a set temperature. In the low-temperature stage of calcination, residual solvents and moisture further evaporate. As the temperature rises to the intermediate temperature stage, polyvinyl butyral, acting as a binder and pore-forming agent, and polyethylene glycol, acting as a binder aid, begin to undergo thermal oxidative decomposition reactions. Their molecular chains break, eventually decomposing completely into small gas molecules such as carbon dioxide and water vapor, which escape. The spaces originally occupied by organic polymers become interconnected or isolated pores, thus forming a three-dimensional porous structure within the particles. When the temperature further increases to the high-temperature stage, solid-state reactions and sintering mainly occur: at the particle interface of La0.9Ca0.1FeO3 powder and Gd0.2Ce0.8O2 powder, atoms diffuse and rearrange, and the two phases achieve close bonding, forming a stable, grain-sized, dual-phase ceramic composite structure. This step ultimately yields a ceramic material that simultaneously possesses three major characteristics: "two-phase composite" in composition, "porous" in structure, and "spherical" in macroscopic morphology.

[0029] This invention discloses a method for preparing porous spherical dual-phase ceramic materials. Steps S1 and S2 prepare pure-phase powders of the active and promoting phases according to precise stoichiometric ratios, ensuring excellent crystal structure and intrinsic properties of each phase. Step S3, through composite ball milling, achieves uniform dispersion and mechanical activation of the two phases at the microscale. Step S4, by preparing a special solution, and step S5, by mixing and grinding, cleverly combines functional organic materials with inorganic powders to obtain a plastic material, laying the foundation for equipment-free molding. Step S6, through a highly innovative strip-ball forming method, eliminates reliance on expensive specialized equipment while achieving precise and convenient control of spherical morphology. Step S7, through drying, imparts strength to the green body. Finally, step S8, through high-temperature calcination, allows the organic pore-forming components to decompose and escape, forming a porous structure, while the inorganic dual-phase material is sintered. These eight interconnected and synergistic steps constitute a complete, efficient, and low-cost preparation technology solution.

[0030] Example 2: This invention provides a porous spherical La0.9Ca0.1FeO3-Gd0.2Ce0.8O2 dual-phase ceramic material for thermochemical fuel production. This material comprises a La0.9Ca0.1FeO3 perovskite phase and a Gd0.2Ce0.8O2 fluorite phase, which are composite to form a dual-phase ceramic structure.

[0031] Among them, the La0.9Ca0.1FeO3 perovskite phase serves as the main redox active phase, used for the release and replenishment of lattice oxygen during thermochemical cycling; the Gd0.2Ce0.8O2 fluorite phase serves as the oxygen migration promoting phase and structural stabilizing phase, used to improve the material's oxygen ion conductivity, oxygen storage and release capacity, and high-temperature structural stability.

[0032] The porous spherical La0.9Ca0.1FeO3-Gd0.2Ce0.8O2 dual-phase ceramic material has a spherical or near-spherical morphology with a diameter of 1–5 mm and an internal porous structure. This porous structure is formed by the thermal decomposition of PVB and polyethylene glycol during calcination, which facilitates the diffusion of gases such as H2O, CO2, H2, CO, and O2 within the particles, thereby improving the gas-solid reaction efficiency in the thermochemical fuel production process.

[0033] 1. Preparation of La0.9Ca0.1FeO3 perovskite powder Weigh out La₂O₃, CaCO₃, and Fe₂O₃ powders according to the stoichiometric ratio required to form La₀.₈Ca₀.₁FeO₃. The molar ratio of La, Ca, and Fe is 9:1:10. Place the weighed powder into a ball mill jar, add 100 mL of anhydrous ethanol as the milling medium, and add agate grinding balls. The mass ratio of powder to agate grinding balls is 1:5.

[0034] The grinding jar was placed in a planetary ball mill for ball milling. The ball mill speed was 240 r / min, and the total grinding time was 48 h. During the ball milling process, the milling was carried out in an alternating forward and reverse rotation pattern, with 30 min of forward rotation, 30 min of rest, and 30 min of reverse rotation, and this cycle was repeated.

[0035] After ball milling, the resulting slurry was poured into a beaker and placed in a drying oven for drying. The drying temperature was 70℃, and the drying time was 12 hours. After drying, a mixture of powder and grinding balls was obtained, which was then sieved to obtain dried powder.

[0036] The dried powder was placed in a tube furnace and calcined in air. The calcination temperature was 1200℃, the holding time was 6 h, the heating rate was 5℃ / min, and the cooling rate was 5℃ / min. After calcination, the powder was ground to obtain La0.9Ca0.1FeO3 perovskite powder.

[0037] 2. Preparation of Gd0.2Ce0.8O2 fluorite phase powder Weigh Gd₂O₃ and CeO₂ powders according to the stoichiometric ratio required to form Gd₀.₂Ce₀.₈O₂. The molar ratio of Gd to Ce is 2:8. Place the weighed powder into a ball mill jar, add 100 mL of anhydrous ethanol as the milling medium, and add agate grinding balls. The mass ratio of powder to agate grinding balls is 1:5.

[0038] The ball mill jar was placed in a ball mill for ball milling. The ball mill speed was 240 r / min, and the total ball milling time was 48 h. During the ball milling process, an alternating operation mode of 30 min forward rotation, 30 min stop, and 30 min reverse rotation was adopted.

[0039] After ball milling, the resulting slurry was poured into a beaker and placed in a drying oven to dry. The drying temperature was 70℃, and the drying time was 12 hours. After drying, the powder was separated from the grinding balls to obtain dried powder.

[0040] The dried powder was placed in a tube furnace and calcined in air. The calcination temperature was 1200℃, the holding time was 6 h, the heating rate was 5℃ / min, and the cooling rate was 5℃ / min. After calcination, the powder was ground to obtain Gd0.2Ce0.8O2 fluorite phase powder.

[0041] 3. Preparation of La0.9Ca0.1FeO3-Gd0.2Ce0.8O2 dual-phase powder The prepared La0.9Ca0.1FeO3 perovskite powder and Gd0.2Ce0.8O2 fluorite phase powder were weighed at a mass ratio of 1:1 and placed into a ball mill jar. 100 mL of anhydrous ethanol was added to the ball mill jar, and agate grinding balls were added, with a powder to agate grinding ball mass ratio of 1:5.

[0042] The ball mill jar was placed in a ball mill for compound ball milling. The ball mill speed was 240 r / min, and the ball milling time was 48 h. During the ball milling process, an alternating operation mode of 30 min forward rotation, 30 min stop, and 30 min reverse rotation was adopted.

[0043] After ball milling, the resulting slurry was placed in a drying oven for drying. The drying temperature was 70℃, and the drying time was 12 hours. After drying, the powder was separated from the grinding balls to obtain a La0.9Ca0.1FeO3-Gd0.2Ce0.8O2 dual-phase powder.

[0044] 4. Preparation of PVB ethanol solution Weigh out PVB granules and anhydrous ethanol according to a mass ratio of PVB powder to anhydrous ethanol of 5:95. Add the PVB granules to the anhydrous ethanol, heat at 50°C and stir thoroughly until the PVB powder is completely dissolved to obtain a 5% PVB ethanol solution for later use.

[0045] PVB, or polyvinyl butyral, is used to improve the plasticity of mud-like materials and the stability of spherical particle molding, and decomposes to form a porous structure during subsequent calcination.

[0046] 5. Preparation of mud-like materials The La0.9Ca0.1FeO3-Gd0.2Ce0.8O2 biphase powder, 5% PVB ethanol solution, and polyethylene glycol were weighed and mixed at a mass ratio of 6:3:1. PVB serves as a binder, molding aid, and pore-forming component; polyethylene glycol acts as a binder, improving the plasticity of the mud-like material and decomposing to form a porous structure during subsequent calcination.

[0047] The mixture above is placed in a mortar and ground and stirred thoroughly to ensure that the biphasic powder, PVB ethanol solution and polyethylene glycol are evenly mixed to obtain a plastic mud-like material.

[0048] In this embodiment, the porosity of the porous spherical ceramic material obtained by subsequent calcination can be controlled by adjusting the proportion of 5% PVB ethanol solution added to change the content of organic binder and pore-forming components in the mud-like material. Preferably, the mass ratio of the duplex powder, 5% PVB ethanol solution, and polyethylene glycol is 6:3:1.

[0049] 6. Forming of spherical particles Each time, weigh 1g of the mud-like material, roll it into a strip with a diameter of 1–5mm, and then place the strip into a ball-rolling device with a diameter of 1–5mm for kneading and shaping to obtain mud-like spherical particles with a diameter of 1–5mm.

[0050] The ball-forming device can be manufactured using 3D printing or purchased directly. By changing the ball-forming device with different diameters, mud-like spherical particles of different diameters can be produced. This molding method does not require a spray granulator, extrusion spheroidizer, or other specialized granulation equipment, and is characterized by simple equipment, convenient operation, and low cost.

[0051] 7. Drying treatment The obtained mud-like spherical particles were placed in a drying oven for drying. The drying temperature was 150℃, and the drying time was 10 hours. After drying, dried spherical particles with a certain mechanical strength were obtained.

[0052] 8. Secondary calcination and the acquisition of porous spherical ceramic materials The dried spherical particles were placed in a muffle furnace for calcination. The calcination temperature was 900℃, the holding time was 6 hours, the heating rate was 2℃ / min, and the cooling rate was 2℃ / min. During the calcination process, PVB and polyethylene glycol underwent thermal decomposition and were discharged, resulting in a porous structure inside the spherical particles.

[0053] After calcination, a porous spherical La0.9Ca0.1FeO3-Gd0.2Ce0.8O2 dual-phase ceramic material for thermochemical fuel production is obtained, with a spherical diameter of 1–5 mm.

[0054] The material prepared by this invention consists of a La0.9Ca0.1FeO3 perovskite phase and a Gd0.2Ce0.8O2 fluorite phase, which combines the redox activity of perovskite with the oxygen migration ability of Ce-based oxides, thus improving the oxygen exchange performance in the thermochemical fuel production process.

[0055] This invention introduces the Gd0.2Ce0.8O2 phase through a two-phase composite method, which can improve the oxygen ion migration ability and high-temperature structural stability of the material, and is beneficial to improving the stability of the material in multiple redox cycles.

[0056] The material prepared by this invention has a spherical or near-spherical structure, which is more suitable for fixed bed, moving bed or fluidized bed reactor applications than powder materials, and helps to reduce bed pressure drop and improve gas-solid contact uniformity.

[0057] This invention utilizes PVB ethanol solution and polyethylene glycol as molding and pore-forming components. After drying and calcination, a porous spherical structure is formed, which facilitates the diffusion of reactant gases inside the particles and improves the thermochemical reaction rate.

[0058] This invention can prepare porous ceramic microspheres of different diameters by changing the ball-making device of different diameters, and can adjust the particle size according to different reactor types and bed requirements, thus providing high process flexibility.

[0059] The ball-making device used in this invention can be prepared by 3D printing or purchased directly. It does not require a spray granulator, extrusion spheronizer or other special granulation equipment, and has the advantages of simple equipment, convenient operation and low cost.

[0060] This invention can control the porosity of porous spherical ceramic materials by adjusting the addition ratio of PVB ethanol solution, thereby achieving adjustable pore structure, which is beneficial for optimizing gas diffusion and reaction activity according to the requirements of thermochemical fuel production reactions.

[0061] The preparation method of this invention is simple and mainly includes solid-phase ball milling, calcination, composite ball milling, bonding and molding, drying and secondary calcination, which is suitable for preparing millimeter-sized porous spherical dual-phase ceramic particles.

[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A porous spherical dual-phase ceramic material, characterized in that, include: La 0.9 Ca 0.1 FeO3 perovskite phase and Gd 0.2 Ce 0.8 O2 fluorite phase, the two are combined to form a two-phase ceramic structure; the porous spherical two-phase ceramic material has a spherical or near-spherical morphology and a porous structure inside.

2. The porous spherical dual-phase ceramic material according to claim 1, characterized in that, The porous spherical dual-phase ceramic material has a diameter of 1-5 mm.

3. The porous spherical dual-phase ceramic material according to claim 1, characterized in that, The porous structure is formed by the thermal decomposition of polyvinyl butyral and polyethylene glycol during calcination.

4. The porous spherical dual-phase ceramic material according to claim 1, characterized in that, The porous spherical dual-phase ceramic material is used in thermochemical fuel production reactions, including steam cracking to produce hydrogen, carbon dioxide cracking to produce carbon monoxide, or co-cracking of steam and carbon dioxide to produce syngas.

5. A method for preparing porous spherical dual-phase ceramic materials as described in any one of claims 1 to 4, characterized in that, Includes the following steps: S1, Preparation of La 0.9 Ca 0.1 FeO3 perovskite powder; S2, Preparation of Gd 0.2 Ce 0.8 O2 fluorite phase powder; S3, the La 0.9 Ca 0.1 FeO3 perovskite powder and the Gd 0.2 Ce 0.8 O2 fluorite phase powder was subjected to composite ball milling to obtain La 0.9 Ca 0.1 FeO3- Gd 0.2 Ce 0.8 O2 biphase powder; S4. Prepare a polyvinyl butyral ethanol solution; S5. Mix and grind the biphase powder, polyvinyl butyral ethanol solution and polyethylene glycol to obtain a plastic mud-like material; S6. Roll the mud-like material into strips and place them in a ball-forming machine to form mud-like spherical particles; S7. Dry the mud-like spherical particles to obtain dried spherical particles; S8. The dried spherical particles are calcined to obtain the porous spherical dual-phase ceramic material.

6. The method according to claim 5, characterized in that, In step S1, The La 0.9 Ca 0.1 FeO3 perovskite powder is prepared by the following steps: La₂O₃, CaCO₃, and Fe₂O₃ powders are weighed according to a molar ratio of La:Ca:Fe of 9:1:

10. Anhydrous ethanol and grinding balls are added, and the mixture is ball-milled. The ball-milled slurry is dried, calcined, and ground to obtain La₂O₃ powder. 0.9 Ca 0.1 FeO3 perovskite powder.

7. The method according to claim 5, characterized in that, In step S2, The Gd 0.2 Ce 0.8 O2 fluorite phase powder was prepared by the following steps: Gd2O3 and CeO2 powders were weighed according to a molar ratio of Gd to Ce of 2:8, anhydrous ethanol and grinding balls were added, and the mixture was ball-milled. The ball-milled slurry was dried, calcined, and ground to obtain Gd2O3 powder. 0.2 Ce 0.8 O2 fluorite phase powder.

8. The method according to claim 5, characterized in that, In step S3, the La 0.9 Ca 0.1 FeO3 perovskite powder and Gd 0.2 Ce 0.8 The mass ratio of O2 fluorite phase powder is 1:

1.

9. The method according to claim 5, characterized in that, In step S5, the La 0.9 Ca 0.1 FeO3-Gd 0.2 Ce 0.8 The mass ratio of O2 biphase powder, polyvinyl butyral ethanol solution, and polyethylene glycol is 6:3:1, and the mass fraction of the polyvinyl butyral ethanol solution is 5%. The porosity of the final porous spherical duplex ceramic material can be controlled by adjusting the proportion of polyvinyl butyral ethanol solution added.

10. The method according to claim 5, characterized in that, The forming diameter of the ball-making device is 1-5 mm. By changing the ball-making device with different diameters, porous spherical dual-phase ceramic materials with different ball diameters can be prepared. The ball-making device is prepared by 3D printing.